2016
DOI: 10.1007/s00429-016-1286-x
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state test–retest reliability of a priori defined canonical networks over different preprocessing steps

Abstract: Resting-state functional connectivity analysis has become a widely used method for the investigation of human brain connectivity and pathology. The measurement of neuronal activity by functional MRI, however, is impeded by various nuisance signals that reduce the stability of functional connectivity. Several methods exist to address this predicament, but little consensus has yet been reached on the most appropriate approach. Given the crucial importance of reliability for the development of clinical applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 93 publications
(176 reference statements)
1
37
1
Order By: Relevance
“…Moreover, it increased the effects of head motion on functional connectivity. This is in line with the results of previous studies: Varikuti et al found that CompCor was disadvantageous for both within or between‐participant reliability [Varikuti et al, ] while Shirer et al found a negative impact of CompCor specifically on test‐retest reliability [Shirer et al, ]. There may be several reasons for this decrease in reliability.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, it increased the effects of head motion on functional connectivity. This is in line with the results of previous studies: Varikuti et al found that CompCor was disadvantageous for both within or between‐participant reliability [Varikuti et al, ] while Shirer et al found a negative impact of CompCor specifically on test‐retest reliability [Shirer et al, ]. There may be several reasons for this decrease in reliability.…”
Section: Discussionsupporting
confidence: 90%
“…We also observed that nuisance regression shifts the distribution of age effects to lower values (except for CompCor), but has little effect on the pattern of age effects across connections. It has been suggested previously that reliability of individual connections is most important for the reliability of groupeffects on connectivity [Varikuti et al, 2017]. However, we observed that improved reliability of the age effect was associated with the reliability of each participant's full connectivity matrix (within-participant reliability), but not with the reliability of the individual differences in connectivity estimates in each ROI pair (between-participant reliability).…”
Section: Accounting For Remaining Physiological and Motion Signalscontrasting
confidence: 68%
“…Given that connectivity patterns of all systems differentiated very well between young and old participants, we acknowledge the possibility that the relevant drivers may be of non‐neural origin. In particular, despite of our optimized confound removal [Power et al, ; Satterthwaite et al, ; Varikuti et al, ], we cannot exclude that residual effects related to motion or brain atrophy as well as physiological effects such as macro‐ and microvascular changes and their cumulative impact on hemodynamic signals [D'Esposito et al, ] may have contributed to our findings.…”
Section: Discussionmentioning
confidence: 92%
“…Schilbach et al 2016; Varikuti et al 2016) of neuroimaging meta-analyses to provide robust, functionally specific ROIs to investigate individual task-free data (Lee et al 2012). These can help to constrain the otherwise vast feature space for statistical learning on resting-state data in a functionally meaningful and anatomically specific manner (Wang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This procedure was done separately for men and women ( Sample 1 : 5 males, 5 females; Sample 2 : 4 males, 4 females). No subjects were excluded due to outlier motion parameters (DVARS and FD both displaying zero-centered values) (Salimi-Khorshidi et al 2014; Varikuti et al 2016; Ciric et al 2017). For RSFC analyses, the subject-specific time series for each node of each network were computed as the first eigenvariate of the activity time courses of all gray-matter voxels within 6 mm of the respective peak coordinate.…”
Section: Methodsmentioning
confidence: 99%